(3GdYhdeI heSJbHd GdUQGY GdGbJUGOjs - (3cGed YdGhj(B, (3GdaJdGhjs; (3YGWa(B, (3dGaj eQRhbs ((3YeGf(B:s (3OGQ UaGA(B,s, 2008)
-(3GdGWGQ GdfXQj debhdJj GdYhdeI hGdUQGY (B- (3JGQjNjI GdUQGY GdYQHj GdGSQGFjdj (B-(3GdYhdeI hGdGbJUGO GdSjGSj GdYQHj (B-(3GdJWhQ GdGbJUGOj aj GSQGFjd hJMhdGJg aj Xd GdYhdeI (B-(3GdYQH GRGA GSQGFjd aj GdGbJUGO GdYGdej (B- (3GdUQGY GdGbJUGOj GdYQHj GdGSQGFjdjs
(3GdeQGLY U(B.545 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdCfXeI GdEbJUGOjIs; (3GdEbJUGO GdSjGSjs; (3GdeTcdGJ GdEbJUGOjI hGdELJeGYjIs